PENGARUH STRATEGI PEMECAHAN MASALAH TERHADAP PEROLEHAN BELAJAR SOAL CERITA MATEMATIKA - Agusniarti, Nelly; Marzuki, Marzuki; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is whether there is any influences of problem solving strategy to the acquisition of learning by word problems of Mathematics in Pontianak State Elementary School. This study aims to see whether there is influence of problem-solving strategies on the acquisition of mathematics learning in Pontianak Elementary. The method used is experimental with Pre-Experimental type of One-Group Pretest-Postest Design. The population is Elementary School 11 Pontianak with the sample used is students of class IIIB who consists of 39 learners. The technique used is the measurement technique. Data collection tools in the form of learning acquisition test in essay are 4 questions. Based on statistical calculation from mean Post-Test experimental class 69,34 obtained t_count equal to 41,3070615 and tÂ (Î± = 5% and dk = 39 - 1 = 38) equal to 2,0252. Thus count (41.3070615)> t_table (2.0252), then Ha is accepted. Therefore, it can be concluded that there is an influence in the use of problem-solving strategies on the acquisition of learning word problems of math in Elementary School 11 Pontianak. From the calculation of the effect size (ES), obtained 1.77137939 (pertained high). This means that learning by using problem solving strategies by word problems has a high influence on the acquisition of mathematics learning in the students of third grade of Elementary School 11 Pontianak.Â Keywords: Problem Solving Strategy, Acquisition of Learning, Mathematics